Indonesia and ASEAN’s Refugee Deadlock: Between Regional Commitments and National Sovereignty - Atin Prabandari; Emma Seruni Ketaren; Balya Arung Segara (Indonesian Perspective, 2025)
This paper critically evaluates Indonesia’s involvement with ASEAN in the governance of refugees, contextualizing this within a regional impasse associated with an enduring prioritization of national sovereignty over collective obligations to promote humanitarian response. The paper examines Indonesia’s participation in the Bali Process, its bilateral refugee management efforts and its response to the Rohingya crisis to assess whether Indonesia is a positive or negative influence on the development of a cohesive ASEAN refugee framework. The results underscore the fragmented nature of ASEAN’s approach, driven by the principles of non-interference, the securitization of migration, and the lack of binding legal obligations, that stand in the way of the development of a structured and rights-based approach to asylum. As high-profile as Indonesia has been in demonstrating humanitarian leadership in some crises, it adopts restrictive domestic asylum policies that preclude engagement in foreign policy advocacy for regional solutions. The study contends that unless the region is able to transcend sovereignty-based limitations and adopt necessary institutional reforms, ASEAN’s standing regarding refugee governance will remain compromised.